2021
DOI: 10.2147/ott.s284261
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Inhibits the Growth of Ovarian Cancer Cells Through the Suppression of Mitosis by Down-Regulating the Expression and the Activity of CDK1

Abstract: Introduction Ovarian cancer is one of the most common gynecological cancers worldwide. While, therapies against ovarian cancer have not been completely effective, sinomenine has been proved to have anti-tumor activity in various cancer cells. However, study of its anti-ovarian cancer effect is still rare, and the underlying mechanism has not been elucidated. Therefore, we aim to explore the mechanism of sinomenine anti-ovarian cancer. Materials and Methods The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Sinomenine also promotes cell apoptosis through G0/G1 phase arrest [68]. Recent work has shown that sinomenine inhibits HeyA8 cell growth by inhibiting mitosis and modulating its expression and activity [19]. Sinomenine inhibits proliferation and metastasis in ovarian cancer cells in a time-and concentrationdependent manner and may inhibit metastasis while reversing EMT and decreasing β-catenin nuclear accumulation.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Sinomenine also promotes cell apoptosis through G0/G1 phase arrest [68]. Recent work has shown that sinomenine inhibits HeyA8 cell growth by inhibiting mitosis and modulating its expression and activity [19]. Sinomenine inhibits proliferation and metastasis in ovarian cancer cells in a time-and concentrationdependent manner and may inhibit metastasis while reversing EMT and decreasing β-catenin nuclear accumulation.…”
Section: Cervical Cancermentioning
confidence: 99%
“…X.Y. Qu and team reported that SIN inhibited the proliferation (IC 50 = 1.56 mM) and colony-formation ability of ovarian cancer HeyA8 cells by downregulating CDK1, reducing p-CDK (Thr161) and p-Histone H3 (Ser10) [ 36 ]. The previous year, F. Gao et al reported the antitumor activity and mechanism of Mufangji decoction (MFJD), of which SIN is a component in preventing lung cancer.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Another compound 2 (35) (10 mM) displayed neuroprotective effects by inhibiting the oxidative damage induced via β-amyloid 25-35 in PC-12 cells [224]. The authors reported that SIN derivative 3A (36) showed an obvious inhibitory effect on CFLL-2 (IC 50 was 2.3 mM), and the inhibitory rate of NO production on macrophages was 97.1%. It can alleviate hematopoietic cell damage via reducing the activity of stimulated CD8 + T cells, reducing cell surface antigen CD69 expressed via activating T cells, impair aerobic glycolysis, and inhibit the release of IFN-γ and TNF-α in mouse CTL line CFLL-2 [225].…”
Section: Other Bioactivities Of Sin Derivativesmentioning
confidence: 99%
“…SIN has anti-inflammatory effects and has been used to treat rheumatoid diseases in humans (Lin et al, 2022b;Chen et al, 2022). In recent years, SIN and its derivatives have been reported to have strong anti-tumor activity against various tumors, including BC (Xu et al, 2021b), prostate (Xu et al, 2019), papillary thyroid (Zhang et al, 2022b), breast (Li et al, 2022b;Gao et al, 2022), ovarian (Qu et al, 2021), and lung cancers (Bai et al, 2021). SIN can inhibit cell proliferation (Sun et al, 2018a;He et al, 2018), induce apoptosis (Liu et al, 2019) and arrest the cell cycle at the G0/G1 phase in various cancers (Yang et al, 2021a).…”
Section: Sinomeninementioning
confidence: 99%